Uniformly Boundedness in Nonlinear Volterra Integro-Differential Equations with Delay - Tunç, Cemil; Mohammed, Sizar Abid (Journal of Applied Nonlinear Dynamics, 2026)
We pay our attention to a number of nonlinear Volterra integrodifferential equations of first order, VIDEs, with constant retardation. The uniform boundedness, UB, of the solutions, to that VIDEs is investigated via the Lyapunov functionals, LFs, method. The results obtained improve and complement a number of works found in the literature. The novelty and originality of this article is that it improves and extends the results found in the literature from the cases of the without delay to the more general cases with delay by constructing some new LFs.